Vertical community patterns of Labyrinthulomycetes protists reveal their potential importance in the oceanic biological pump. (16th August 2021) - Bai, Mohan; Xie, Ningdong; He, Yaodong; Li, Jiaqian; Collier, Jackie L.; Hunt, Dana E.; Johnson, Zackary I.; Jiao, Nianzhi; Wang, Guangyi
Summary: The biological pump plays a vital role in exporting organic particles into the deep ocean for long‐term carbon sequestration. However, much remains unknown about some of its key microbial players. In this study, Labyrinthulomycetes protists (LP) were used to understand the significance of heterotrophic microeukaryotes in the transport of particulate organic matter from the surface to the dark ocean. Unlike the sharp vertical decrease of prokaryotic biomass, the LP biomass only slightly decreased with depth and eventually exceeded prokaryotic biomass in the bathypelagic layer. Sequencing identified high diversity of the LP communities with a dominance of Aplanochytrium at all depths. Notably, ASVs that were observed in the surface layer comprised ~20% of ASVs and ~60% of sequences in each of the deeper (including bathypelagic) layers, suggesting potential vertical export of the LP populations to the deep ocean. Further analyses of the vertical patterns of the 50 most abundant ASVs revealed niche partitioning of LP phylotypes in the pelagic ocean, including those that could decompose organic detritus and/or facilitate the formation of fast‐sinking particles. Overall, this study presents several lines of evidence that the LP can be an important component of the biological pump through their multiple ecotypes in the pelagic ocean.